2023
DOI: 10.1002/anie.202218218
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strategy to Drive the Intracellular Uptake of Lipid Nanoparticles for Photodynamic Therapy

Abstract: Nanoparticles' uptake by cancer cells upon reaching the tumor microenvironment is often the ratelimiting step in cancer nanomedicine. Herein, we report that the inclusion of aminopolycarboxylic acid conjugated lipids, such as EDTA-or DTPA-hexadecylamide lipids in liposome-like porphyrin nanoparticles (PS) enhanced their intracellular uptake by 25-fold, which was attributed to these lipids' ability to fluidize the cell membrane in a detergent-like manner rather than by metal chelation of EDTA or DTPA. EDTA-lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In summary, four main formulations of liposome were synthesized for each metal complex. The first formulation design was based on a successful formulation of porphyrin‐based liposome for cancer PDT, [ 22 ] which consists of 40% cholesterol and 5% 1,2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐ N ‐[methoxy(polyethylene glycol)‐2000] (PEG‐lipid). Building upon this formulation, we designed and synthesized Re‐HC and Ir‐HC liposomes (HC indicating high cholesterol content) containing 40% cholesterol, 5% PEG‐lipid, 25% Re‐lipid or Ir‐lipid, and 30% distearoylphosphatidylcholine (DSPC) as the base lipid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, four main formulations of liposome were synthesized for each metal complex. The first formulation design was based on a successful formulation of porphyrin‐based liposome for cancer PDT, [ 22 ] which consists of 40% cholesterol and 5% 1,2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐ N ‐[methoxy(polyethylene glycol)‐2000] (PEG‐lipid). Building upon this formulation, we designed and synthesized Re‐HC and Ir‐HC liposomes (HC indicating high cholesterol content) containing 40% cholesterol, 5% PEG‐lipid, 25% Re‐lipid or Ir‐lipid, and 30% distearoylphosphatidylcholine (DSPC) as the base lipid.…”
Section: Resultsmentioning
confidence: 99%
“…This design was based on our recent discovery of incorporating EDTA‐lipid into liposomal nanoparticles, enabling the fluidization of the cell membrane in a detergent‐like manner to promote intramembrane uptake of nanoparticles. [ 22 ] The third formulation had a lower content of cholesterol (17%) and PEG‐lipid (2%), with dipalmitoylphosphatidylcholine (DPPC) as the base lipid instead of DSPC. These formulations were named Re‐LC and Ir‐LC, where LC indicates the low cholesterol content.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancing the cellular uptake efficiency of PBAs is critical to improve their therapeutic effect. , Recently, Ho et al reported an EDTA-lipid incorporated-porphysome (ePS) which was formed by a mixture of porphyrin-based lipids and EDTA-lipids . The ePS could achieve >95% PDT cell killing efficiency, which was 19 times higher than EDTA-lipids-free porphysome.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…82,210 Recently, Ho et al reported an EDTA-lipid incorporated-porphysome (ePS) which was formed by a mixture of porphyrin-based lipids and EDTA-lipids. 211 The ePS could achieve >95% PDT cell killing efficiency, which was 19 times higher than EDTA-lipidsfree porphysome. The result demonstrated that EDTA could improve the cell uptake efficiency in certain circumstances.…”
Section: Disease Treatment 321 Photodynamic Therapy (Pdt) and Phototh...mentioning
confidence: 99%
“…[16][17][18] Nanoscale DDSs may help accumulate PSs in tumor by the enhanced permeability and retention (EPR) effect. Different types of DDSs have been developed for the delivery of PDT PSs, including inorganic nanoparticles, [19][20][21] cross-linked polymeric nanoparticles, 22,23 vesicles [24][25][26][27] and organic framework materials. 28,29 The key criteria for the design of PDT DDSs include facile preparation, stable encapsulation during circulation, good biocompatibility and improved efficacy.…”
Section: Introductionmentioning
confidence: 99%